An investigation of the basis of judgments of remembering and knowing (JORKs) - Soderstrom, Nicholas C., author; Rhodes, Matthew G., advisor; Cleary, Anne M., committee member; Davalos, Deana B., committee member; Rickey, Dawn, committee member (Colorado State University. Libraries, 2012)
Previous research indicates that prospective metamemory accuracy can be improved if participants are asked to monitor whether contextual details will be remembered or not (i.e., judgments of remembering and knowing; JORKs), as opposed to monitoring confidence (i.e., judgments of learning; JOLs), an important finding given that accurate memory monitoring has been linked to effective learning. Three experiments investigated whether the advantage for JORK is due to these judgments being based more on retrieval processes than JOLs. Experiment 1 showed that JORKs resemble retrospective confidence judgments (RCJs)--judgments known to be based on retrieval processes--in some ways but not in others. Experiment 2 demonstrated that JORKs benefit less from a delay than JOLs when judgments are made under some circumstances but not others, and Experiment 3 showed that JORKs are less susceptible to a manipulation of encoding fluency than JOLs. Thus, overall, the results provide mixed support for the idea that JORKs are more reliant on retrieval processes than JOLs, reinforcing the need for future research on this topic.
Keywords: metacognition; memory predictions; metamemory; episodic memory; judgments of learning